(untitled) (Journal of the College of Basic Education, 2022)
In this work, we apply Wilcoxon singed-rank test upon three nonparametric random samples taken from serum thyroxin hormones which are T.S.H, T3,and T4 respectively with each sample size n=25, to test the hypothesis about population mean and tabulate the data. After applying the test we conclude that the chosen population means are accepted for all samples.